Skuas (Stercorarius spp.) moult body feathers during both the breeding and inter-breeding periods: implications for stable isotope investigations in seabirds - Graña Grilli, Maricel; Cherel, Yves (Ibis)
Seabirds are mostly thought to moult during the inter-breeding period and the isotopic values of their feathers are often therefore assumed to relate to their assimilated diet during such periods. We observed Brown Skuas Stercorarius antarcticus lonnbergi and South Polar Skuas Stercorarius maccormicki moulting on a breeding site at King George Island, Antarctica. This raises concerns about the reliability of using stable isotopes in feathers to infer feeding localities of birds during the inter-breeding period. We analysed the δ13C and δ15N values of growing and fully grown body feathers collected from the same individuals. For both species, δ13C values of growing feathers indicated feeding areas in the Antarctic zone (breeding grounds), whereas most fully grown feathers (100% for South Polar Skuas and 93.3% for Brown Skuas) could be assigned to northern latitudes (non-breeding grounds). However, a few fully grown body feathers of Brown Skuas (6.7% of the feathers, belonging to two birds) showed isotopic values that indicated moult in the Antarctic zone. As the growth period of those feathers was unknown, they could not be used with confidence to depict the foraging behaviour of the birds during the non-breeding period. Although precautions must be taken when inferring dietary information from feathers in seabirds where the moulting pattern is unknown, this study shows that if the development stage of a feather (growing/fully grown) is identified, then dietary information from both breeding and non-breeding seasons can be obtained on the same individual birds. Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Cherel, Yves. Centre d'Etudes Biologiques de Chizé; Francia